STRATEGI MAHASISWA DALAM MEYELESAIKAN TUGAS AKHIR BERBASIS KECERDASAN BUATAN CHATGPT - Wahab, Wirdayani (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2024)
Artificial intelligence (AI) has a variety of important impacts on many aspects of life and industry. AI drives innovation by identifying patterns and trends that may not be visible to humans, enabling new discoveries in fields such as science, technology, and education. In the world of education, especially for students in completing their final assignments, this artificial intelligence is very helpful. However, there are many problems if you use this artificial intelligence incorrectly. This article describes how students' strategies are in completing final assignments based on artificial intelligence through chatGPT but do not violate scientific ethics. The method used in this study is a qualitative method using informants from students and lecturers and data is collected through interviews and analyzed using SWOT analysis. The results of the study show that the strategy that can be used by students in completing final assignments based on artificial intelligence chatGPT is a diversification strategy, namely through modification, through original concepts supported by artificial intelligence in finding references will produce scientific work as a final assignment that can be scientifically accounted for.